(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2022)
This article comes from my experiences as a History teacher in high schools from the suburbs in Rosario. It reflects on the changes that the teaching of this discipline needs in the context of postpandemics. Tradicional high school teaching has been in discussion for some time now, specially History teaching with its particularities, but Covid-19 pandemics emphasized its weaknesses. Strategies like the searching of “priority contents” and the using of TICs revealed themselves insufficient. Back to face-to-face clases, the system exhaustion is more stressed, especially in the suburbs, where students lack of material goods and the bonds that hold them are often weak. In this context they have difficulties adquiring skills like text comprehension and oral and written expression, which they need for learning History.